Pro- and Anti-Inflammatory Cytokines during Immune Stimulation: Modulation of Iron Status and Red Blood Cell Profile - A. M. Koorts; P. F. Levay; P. J. Becker; M. Viljoen (Mediators of Inflammation)
Forty-eight patients were subdivided according to C-reactive protein (CRP) levels, resulting in 19 patients with normal (2.8 ± 2.8 mg/L) and 29 with elevated (82.2 ± 76.2 mg/L) CRP levels. The elevated CRP group had iron and red blood cell (RBC) profiles characteristic of chronic immune stimulation (CIS), and the normal CRP group, profiles of true iron deficiency. Normal relationships between storage iron, bioavailable iron, and RBC indices were absent in the elevated CRP group—implying the role of iron as major determinant of the RBC profile to be diminished during CIS. The elevated CRP group had significant increases in proinflammatory cytokines (INF-γ, TNF-α, Il-1β, Il-6, and Il-8). Anti-inflammatory cytokine levels were normal, except for Il-10, supporting previous indications that Il-10 contributes to reducing bioavailable iron. Regression analysis suggested decreases in transferrin to be related to increases in Il-8 and an increase in ferritin to be related to a decrease in Il-12 levels. TGF-β levels were positively related to transferrin and negatively to ferritin.